Temporal Translation of Matter Exploring the Theoretical Foundations for Backward and Forward Temporal Translation of Matter Inferred from Remote Viewing and Precognition Findings - Amorim Boyle, Benjamin J. (Journal of Scientific Exploration, 2025)
This paper explores the possibility that matter may be capable of traveling through time, an idea derived from the convergence of anomalous findings in parapsychological research and advanced theoretical interpretations in contemporary physics. Studies in precognition and remote viewing—despite their controversial status—have repeatedly produced results suggesting that information can be accessed outside the conventional forward flow of time. Interpreted within a physicalist paradigm where information is inextricably tied to energy and matter, these anomalies imply that if information can move temporally backward and forward, then energy and mass may also achieve temporal displacement. While quantum mechanics and relativistic models of spacetime do not categorically exclude retrocausality, the extrapolation of this concept from intangible information flows to the tangible realm of matter demands rigorous scrutiny. This paper integrates the empirical record from parapsychological experiments with the theoretical foundations of mass-energy equivalence and quantum retrocausality to propose a conceptual framework for matter’s temporal translation. In acknowledging the speculative nature of this endeavor, it nonetheless aims to motivate more systematic investigations, encourage interdisciplinary discourse, and clarify the methodological and theoretical challenges that must be overcome. Ultimately, this analysis seeks to open a constructive dialogue on whether the once-unthinkable notion of matter traversing time may merit a place within the broader tapestry of contemporary physical theory.